The Gospel of John ; v. 2 a commentary - Keener, Craig S. 1960- (Peabody, MA Hendrickson, 2003)
Contents : v. 2 : Chapter 11:1 - 21:25. Includes bibliographical references and index.
Pagination follows from v. 1 (835-1636). Table of contents included in v. 1.
Keywords: Bible. N.T. John -- commentaries